Matt Mullican - Representing the work - Mullican, Matt 1951- (Musée des Arts Contemporains au Grand-Hornu, 2020)
This richly illustrated monograph accompanies the first Belgian retrospective of the work of Matt Mullican. Since the early 1970s, Matt Mullican has sought to structure the world and to understand it using various supports (stone slabs, flags and banners, stained-glass windows or computer assisted compositions, etc.) to establish a truly personal cosmology. This mental map, which he named "the five worlds", refers to the various levels of perception with which he associates colours (yellow for art, red for ideas, etc.). In this way the artist will invade the space of the MAC's to plunge the visitor into the heart of his original universe and confront us with the numerous aspects which characterise human life. Exhibition: MACs, Grand Hornu, Charleroi, Belgium (16.02.-18.10.2020)
Impressum: Cette publication paraît à l'occasion de l'exposition "Matt Mullican. Representing the Work", Musée des Arts Contemporains au Grand-Hornu (MACS), 16.02 - 18.10.2020
Keywords: Mullican, Matt -- 1951-; Zeichnung; Installation -- Kunst; Ausstellungskatalog -- Musée des Arts Contemporains de la Communauté Française de Belgique -- 16.02.2020-18.10.2020 -- Hornu; Bildband